Desain Dan Rekayasa Alat Pengkristal Gula Semut Menggunakan Piringan Crusher - Atmoko, Tri Atmoko, Tri Widodo Besar Riyadi. ST. MSc. Ph.D (2017)
The objective of the research was to design and engineer the tool to crystallize coconut sugar or palm sugar from bar shape into powder by using the disc crusher (crusher), and determine the effect of the crusher speed on the diameter of the powder sugar. The rotation crusher was designed low with consideration for keeping and compromising the quality of the sugar quality especially in terms of color, smell and flavor. Tool design process crystalliser sugar was carried out using SolidWorks software 2014, while the calculation only includes the shaft of pulley and the transmission system of the tool. Operation and testing of the tools was designed using four variations of the rotation crusher, which are 70 rpm, 80 rpm, 90 rpm and 100 rpm. The tests of the micro photograph on a grain of sugar has described the size of the diameter of grain of sugar, with wariation of the rotation speed of the crusher. Modification of the sugar crystalliser tool shows that the mechanism of transmission system using acombination of V-Belt and Gearbox can generate the rotation crusher to 70-100 rpm. The calculation of the production capacity of sugar before and after the use of a crystalliser shows that there is a significant increase by 350%. The test results of the micro photograph of the sugar grain diameter showed that the rotation crusher 70, 80, 90 and 100 rpm produces sugar with a grain size specifications size of 2200 μm, 1551 μm, 1222 μm dan 854 μm. Based on this study, the 100 rpm rotation is the most suitable rotation speed to produce sugar with the size sugar grain diameter of 854 lm, which is suitable with the market demand. Thus, the application of these tools can increase production capacity and produce the diameter size of sugar grain in accordance with market demand.